EXPLANATION AND ASSISTANCE OF WASTE MANAGEMENT IN SELANBAWAK VILLAGE ELEMENTARY SCHOOL - Saputra, I Made Valentino Rossi; Ari Lestari, Ni Kadek; Anggraeni Kesuma, Ni Putu Regita; Arimbawa, Komang Gede; Purnama Sari, Desak Made Febri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Trash is something that is always there in everyday life. Everyone active will produce waste and the same thing happened in Selanbawak Village, Marga sub-district. The problem with this work program is that the waste management process that has been carried out has not been included in the good and correct category because most of the waste management process is carried out by improper disposal and by incineration. The purpose of this work program is to improve the existing waste management system in Selanbawak Village. The participants used in this work program are elementary school students in Selanbawak village. The results of this work program state that the knowledge of elementary school children about the importance of waste management in Selanbawak Village is still not good. This is due to the lack of socialization and direct waste management assistance and inadequate facilities and infrastructure. The level of awareness of elementary school students on the importance of waste management is also still low. Suggestions that can be given are periodic socialization of proper and proper waste management, procurement of organic and inorganic waste bins, and the establishment of a waste bank in Selanbawak Village.